Black American males in higher education diminishing proportions - Frierson, Henry T. 1944-; Pearson, Willie, 1945-; Wyche, James H. (Diversity in higher education ;, 2009)
This is the first of two volumes that specifically addresses the subject of the disproportional decline of Black American Males in higher education. For too long, acknowledgment of this issue has been avoided for fear that it would be clearly and too painfully felt. It is apparent that this issue can no longer be ignored and the need to examine and widely address this situation is now so vivid. This volume, and the next, forthrightly discuss and address the conditions that can be observed today. Collectively, the contributing authors provide critical historical overviews and analyses pertaining to Black American males in higher education and Black Americans of both genders. The contributing authors provide data from which conclusions can be drawn, discussion of the effectiveness of programs, conceptual pieces that address the issue of the presence or lack thereof of Black American males in higher education from a range of perspectives, and the role of the community colleges.